Influence of Illumination and Polarized Moonlight on Light-Trap Catch of Caddisflies (Trichoptera) - Nowinszky László (RESEARCH JOURNAL OF BIOLOGY, 2012)
The study analysed the potential effects of moon phases on the light-trap catches of eight species from seven Trichoptera families. The light-traps operated between 1981 and 2005 at ten Hungarian sampling sites. Relative catches calculated from daily collected data were arranged by the moon phase angle groups within lunar cycle. Linear and non-linear regression analyses were carried out to test the influences of two moonlight variables (illumination of the moon and rate of polarized moonlight) and the collecting distance changing with moon phase angle groups on the averaged relative catch. The relative catch level of caddisflies significantly varied in a species-specific way to changing moonlight characteristics through the lunar month. Two species showed a rising trend of catch levels with increasing moonlight illumination around the full moon period. Only one species expressed significantly increasing relative catches by the increasing theoretical collecting distance caused by the decreasing moonlight illumination between full and new moon. The study demonstrated for the first time the effect of increasing polarized moonlight in the first and last quarter on the flying activity of five caddisfly species. Supposedly, caddisflies use these moonlight characteristics as orientation cues increasing the number of flying and, consequently, captured adults.